Green synthesis and characterization of silver/chitosan/polyethylene glycol nanocomposites without any reducing agent. - Ahmad @ Ayob, Mansor; Mei, Yen Tay; Shameli, Kamyar; Hussein, Mohd. Zobir; Jenn, Jye Lim (MDPI, 2011)
This paper presents the green synthesis of silver nanoparticles (Ag NPs) in aqueous medium. This method was performed by reducing AgNO3 in different stirring times of reaction at a moderate temperature using green agents, chitosan (Cts) and polyethylene glycol (PEG). In this work, silver nitrate (AgNO3) was used as the silver precursor while Cts and PEG were used as the solid support and polymeric stabilizer. The properties of Ag/Cts/PEG nanocomposites (NCs) were studied under different stirring times of reaction. The developed Ag/Cts/PEG NCs were then characterized by the ultraviolet-visible (UV-Vis) spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM) and Fourier transform infrared (FTIR) spectroscopy.